INOVASI PELAMINAN DIKECAMATAN LUBUK BEGALUNG KOTA PADANG - Ardeni, Nofi; Zahri, Wildati; Adriani, Adriani (Journal of Home Economics and Tourism, 2015)
This study aimed to describe the aisle innovation in District LubukBegalung Padang. This type of qualitative research using qualitativeresearch methods. The type of data in the form of primary and secondarydata. The technique of collecting data through observation, interviews,documentation and triangulation. The study concluded innovation aisle,look at innovations parts kasua aisle wood into the aisle seat, a part oftraditional wedding that is not used anymore as: Banta Bulek, Bantakatiak, Rambai-Rambai. The materials used in traditional wedding isvelvet and satin with gold thread sewing, and now has experiencedinnovations that sateen material with sewing lame or tinsel. Colors used intraditional wedding that is red, yellow, green, and black and is nowexperiencing innovation are like the yellow color of gold, silver, purple,blue, pink, and gray. Motifs used in traditional wedding motifs kaluak nails, motive sayik galamai, betel leaf motif and now there is thedevelopment of the old motifs that sarumpun floral, florals sow, butterflymotif. Embroidery techniques used in traditional wedding that gold threadembroidery technique that is done manually or by hand and are nowexperiencing the process of innovation that is embroidered by machine.Keyword : Wedding, Inovation, Lubuk Begalung Subdistric